Screening of Thalassemia Major or Intermedia on Routine Complete Blood Count in An Outpatient Setting (Medical Forum Monthly, 2020)
Objective: To find out the relationship between Red cell distribution width (RDW-CV) and level of fetal hemoglobin on HPLC.Study Design: Prospective, observational cross-sectional studyPlace and Duration of Study: This study was conducted at the Institute of Hematology, Baqai Medical University, Karachi from September 2018 till March 2019 or a period of six months.Materials and Methods: Patients were seen in Baqai Institute of hematology and their blood samples were sent to Hematology laboratory of Dow university Ojha complex, Karachi. A total of 394 consecutive blood samples aged 8 months to 5 years were analyzed for Hb. HPLC. Complete blood count was done immediately on fully automatic hematology analyzer while Hb. HPLC was done the same day on automatic Adam’s Arkray HPLC analyzer.Results: On the basis of RDW-CV, two groups were created as Group 1 & 2 having RDW-CV less than 30.9 and more than 30.9 respectively. Mean RDW and Hb-F levels for group 1(n = 248) and 2 (n = 146) were 18.5, 1.32 % and 35.62 and 65 % respectively.Conclusion: Very high RDW-CV on routine CBC has significant relation to high values of Hb-F which is characteristic laboratory feature of the disease.